Prevalence, Awareness, Treatment, and Control of Hypertension in Romania: Results of the SEPHAR Study - M. Dorobantu; R. O. Darabont; E. Badila; S. Ghiorghe (International Journal of Hypertension)
East European countries have reported high prevalence of Arterial Hypertension (AHT). In order to investigate the data for Romania, we firstly performed a national survey—the Study for the Evaluation of Prevalence of Hypertension and Cardiovascular Risk in Adult Population in Romania (SEPHAR). A representative population was selected using stratified proportional sampling, including 2017 adult subjects, ≥18 years old. The general prevalence of AHT was 44,92%, higher in men (50,17%) than in women (41,11%) (P<.0001) and predominant in rural areas (49,47%) in comparison to the urban ones (41,58%) (P<.02). AHT awareness attended 44,26%, rising with age, significantly lower in men (34,58%) than in women (52,8%) (P<.0006). We have found a 38,85% proportion of treated hypertensive persons, worse for men (30,11%) then for women (46,56%) (P<.003). The rate of AHT control was 19,88%, with no significant differences between gender. In conclusion, we estimated for Romania a high prevalence of AHT, a level of awareness and treatment lower than in many European countries and a rate of treatment control at the inferior limit of the European average. Males, characterized by a higher prevalence of AHT, were also less aware and less treated than women.